Standard specification for steel sheet for porcelain enameling (American Society of Testing Materials, 2009)
This specification covers sheet steel in coils and cut lengths for porcelain enameling. The compositions and processing of these steels are such that articles for porcelain enameling may be fabricated from them and, under proper conditions, enameled. The steels are furnished as Type I, Type II, and Type III. Type I and Type II are supplied in two designations, Commercial Steel and Drawing Steel. Type III steel is interstitial-free and does not require a designation.